La régulation des effectifs de sixième dans un contexte d’assouplissement de la carte scolaire : une enquête sur les logiques des directeurs de collège - Yoann Adler (Recherches en Éducation)
Since the school year began in 2007, leniency regarding the “carte scolaire” has been implemented for secondary school enrolment throughout the nation. The studio deals with regulations drawn up by headteachers at secondary schools in both a city centre and in a town of suburb. The article further exposes the logics expressed by headteachers in order to warrant or deny their actions and those of fellow colleagues: market logic, performance logic, community logic and civic logic. The outcome shows that headteachers speeches at elementary schools will often be performed to address proximity and civil concerns; however, market logic prevails as soon as one particular school suffers from a deficit in student enrolment, or another develops an expansionist and elitist program. Moreover, we note that headteachers use the same logics when they justify the diversification of provision to increase the attractiveness of their school. Some of them use also this way to select their pupils. In this case, the diversification of provision becomes the best method to enter their school.